Impact of Strategic Leadership on Competitive Excellence: A Field Study of Banks in Yemen - Abdulatef Musleh Mohammed Ayedh; Abdulmoghith Yahya Ali Al-Shamsi (University of Science and Technology, Sana’a, Yemen, 2023)
This study aimed to identify the impact of strategic leadership on achieving competitive excellence at banks in Yemen. To achieve this, the descriptive, analytical method was adopted. In this study, the population was all leadership and supervisory staff members in the target banks which amounted to (1710) members, of which (313) members were selected as the study sample by the stratified sampling method. The questionnaire was used to collect data from the study participants. The data was coded, entered and processed by the SPSS 23. In addition, the (PLS- SEM) was used to test the study hierarchical model of two levels, using the program (Smart PLS 3) for structural equation modeling. The reflective model was used to analyze the first level, and the formative model for the second level. The study results revealed that the banks under study show great interest in achieving competitive excellence in all dimensions, as well as in practicing strategic leadership in all aspects. The results also showed that there is a direct, statistically significant effect of strategic leadership on achieving competitive excellence for the banks under study. The study recommended strengthening the practice of leadership, due to its impact on achieving competitive excellence in the banks under study, especially the dimensions of strategic and creative directions for their clear impact in achieving competitive excellence.